2018
DOI: 10.1109/tip.2018.2834830
|View full text |Cite
|
Sign up to set email alerts
|

Improved Random Forest for Classification

Abstract: We propose an improved random forest classifier that performs classification with minimum number of trees. The proposed method iteratively removes some unimportant features. Based on the number of important and unimportant features, we formulate a novel theoretical upper limit on the number of trees to be added to the forest to ensure improvement in classification accuracy. Our algorithm converges with a reduced but important set of features. We prove that further addition of trees or further reduction of feat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
112
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(114 citation statements)
references
References 27 publications
0
112
0
2
Order By: Relevance
“…In particular, the Weka platform [97] was adopted that contains various standard ML algorithms for data mining tasks. Among them, the Trees-J48 (J48) [98], RandF [99], and NN were used. This cost-effective passive method does not require special equipment or signal transmission and intends to statistically analyze features, such as packet size and inter-arrival time analysis.…”
Section: Position Related Aspectsmentioning
confidence: 99%
“…In particular, the Weka platform [97] was adopted that contains various standard ML algorithms for data mining tasks. Among them, the Trees-J48 (J48) [98], RandF [99], and NN were used. This cost-effective passive method does not require special equipment or signal transmission and intends to statistically analyze features, such as packet size and inter-arrival time analysis.…”
Section: Position Related Aspectsmentioning
confidence: 99%
“…The measured rice LAI series are calculated with RS images. In this study, we extract rice region in the study area with a random forest algorithm [67][68][69][70] and then calculate rice LAI through its NDVI obtained from RS images. Previous studies have shown that the exponential empirical model between LAI and NDVI in this area is practicable and most widely used [71].…”
Section: B Data Preparationmentioning
confidence: 99%
“…Using a network simulator the Low Energy Adaptive Clustering Hierarchy (LEACH) was tested to determine as the efficiency of the presented model. [23] Random Forest [26][28] is a learning model for an ensemble that takes tree choice as a fundamental classifier. As the name suggests, with an amount of trees, this algorithm produces the forest.…”
Section: Introductionmentioning
confidence: 99%